Consumerism with Tawhidic paradigm activism through “change the world” project - Mhd. Sarif, Suhaimi (2020)
This study postulates that Tawhidic paradigm activism enables responsible consumption and production consumerism. Responsible consumption and production has been agreed by almost all nations in the World through United Nations Sustainable Development Goals (SDG) 2030 to attain peaceful, prosperous and justice world. This study uses qualitative research through case study of “Change the World” projects with first year students enrolled in Principles and Practice of Management course. After 14 weeks of executing the projects, the study found out that Tawhidic paradigm enhances awareness, understanding and volunteerism in responsible consumption and production among students and industry.